2022
DOI: 10.1371/journal.pone.0277769
|View full text |Cite
|
Sign up to set email alerts
|

Science in motion: A qualitative analysis of journalists’ use and perception of preprints

Abstract: This qualitative study explores how and why journalists use preprints—unreviewed research papers—in their reporting. Through thematic analysis of interviews conducted with 19 health and science journalists in the second year of the COVID-19 pandemic, it applies a theoretical framework that conceptualizes COVID-19 preprint research as a form of post-normal science, characterized by high scientific uncertainty and societal relevance, urgent need for political decision-making, and value-related policy considerati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…This paper finds that the epidemic has changed this model, resulting in more scientific discoveries being disseminated into the public domain through preprinted papers. Several previous studies have shown that journalists have relied more on preprint as a source of news coverage due to the immediacy and ease of accessibility ( 33 , 35 ). It is believed that journalists and the media are “knowledge brokers” who bridge the gap between science and society ( 53 , 54 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This paper finds that the epidemic has changed this model, resulting in more scientific discoveries being disseminated into the public domain through preprinted papers. Several previous studies have shown that journalists have relied more on preprint as a source of news coverage due to the immediacy and ease of accessibility ( 33 , 35 ). It is believed that journalists and the media are “knowledge brokers” who bridge the gap between science and society ( 53 , 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, COVID-19 prompts the dissemination of preprints beyond the academic community to the wider public ( 13 ). Many mainstream journalists have to report on preprints due to the pandemic, which has even become a frequent practice ( 33 35 ). While the role of preprints was well-recognized within the academic community, their dissemination to the public raised concerns.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, preprints have become integrated into traditional media practices, with many journalists actively seeking and reporting on preprints as part of their normal practice. 15 Preprints are also adding to the medical education discourse by eventually becoming published articles in a variety of journals, including those specific to medical education (i.e., in the MEJ-24). The practice of preprints subsequently being published in academic journals is not unique to medical education.…”
Section: Discussionmentioning
confidence: 99%
“…However, several flawed COVID-19-related preprints were covered widely by the media (see Majumder and Mandl, 2020 ; van Schalkwyk et al, 2020 ), adding to a growing quantity of misinformation ( World Health Organisation, 2020 ). The risk that preprint media coverage could mislead audiences is recognised by journalists ( Fleerackers et al, 2022 ); however, journalists are not the only actors shaping public discourse around contingent COVID-19 research. Social media accounts also share, contextualise and amplify scientific findings, including media stories citing preprint research, by sharing hyperlinks with friends and followers.…”
mentioning
confidence: 99%